US-individualized infusion therapy in geriatric patients after emergency abdominal surgery: effect on the development of acute kidney injury - N. V. Momot; N. V. Tumanska; S. I. Vorotyntsev (Patologìâ)
In most elderly patients, prescribing the necessary volume of infusion therapy for the prevention of prerenal acute kidney injury (AKI) requires individualization. It is considered that ultrasound examination of the inferior vena cava (IVC) can be an effective additional method of assessing volemia in this category of patients.